2004
DOI: 10.1902/jop.2004.75.5.709
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ascorbic Acid in Periodontal Ligament Cell Differentiation

Abstract: Our findings indicated that ascorbic acid increases the ALP activity of PDL cells via type I collagen production and also enhances the expression of alpha2beta1 integrin, which is a major receptor of type I collagen. These results suggest that ascorbic acid promotes the osteoblastic differentiation of PDL cells by modulating type I collagen-alpha2beta1 integrin interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 30 publications
3
56
0
3
Order By: Relevance
“…Local differentiation of PDL fibroblasts into osteoblasts and cementoblasts near the bone and cementum surfaces is most likely tightly controlled. Studies have shown that many different factors including both platelet-derived growth factor and transforming growth factor ␤ 1 [Han et al, 2007], BMP2 Yamada et al, 2007], ascorbic acid [Ishikawa et al, 2004;Mimori et al, 2007], and amelogenin and ameloblastin [Zeichner-David et al, 2006] stimulate osteogenic differentiation of PDL fibroblasts. Factors like the transcription factor Msx2 [Yoshizawa et al, 2004], Twist and the proteoglycan PLAP-1/asporin [Yamada et al, 2007] have been implicated in inhibiting such osteogenic differentiation.…”
Section: μMmentioning
confidence: 99%
“…Local differentiation of PDL fibroblasts into osteoblasts and cementoblasts near the bone and cementum surfaces is most likely tightly controlled. Studies have shown that many different factors including both platelet-derived growth factor and transforming growth factor ␤ 1 [Han et al, 2007], BMP2 Yamada et al, 2007], ascorbic acid [Ishikawa et al, 2004;Mimori et al, 2007], and amelogenin and ameloblastin [Zeichner-David et al, 2006] stimulate osteogenic differentiation of PDL fibroblasts. Factors like the transcription factor Msx2 [Yoshizawa et al, 2004], Twist and the proteoglycan PLAP-1/asporin [Yamada et al, 2007] have been implicated in inhibiting such osteogenic differentiation.…”
Section: μMmentioning
confidence: 99%
“…Ishikawa et al studied the effect of ascorbic acid on PDL cells and observed that ascorbic acid increased the ALP activity, which is required for the binding of PDL cells to Type I collagen through 2 beta 1 integrin, whose expression is again increased by ascorbic acid. As Type I collagen production is considered an initial process in the differentiation of PDL cells, it may serve as a potential storage medium [18]. 0.14 g/L potassium phosphate; 0.14 g/L calcium chloride; 0.1 g/L magnesium chloride; and 0.1 g/L magnesium sulfate.…”
Section: Ascorbic Acidmentioning
confidence: 99%
“…It should be noted that this may have consequences for the function of prolylhydroxylase which cofactor is ascorbic acid. Moreover, vitamin C deficiency may influence the collagen structure and extracellular matrix via promotion of the osteoblasts differentiation by modulating type I collagen-α2β1 integrin interactions [40], triggering the aggregated collagensynthesizing cells to organize their extracellular matrix [41], regulating proteoglycans biosynthesis and turnover [42] and altering mRNA levels in collagensynthesizing cells by changing the transcription rates [43]. Additionally, ascorbic acid also induced alkaline phosphatase activity, the expression of mRNAs for proteins that are markers of osteoblastic differentiation, the deposition of calcium [44] and increase of the rate of procollagen secretion from cells into extracellular matrix [45].…”
Section: T a B L E 1 Initial And Final Body Weights And Blood Glucosmentioning
confidence: 99%